Optimalisasi Pembelajaran Pendidikan Jasmani melalui Program Pelatihan dan Pendampingan Aktivitas Fisik di SMAS Pesantren IMMIM - Juhanis Juhanis; Fatoni Fatoni; Andi Saiful Alimsyah; Bahrul Alim; St. Zulaiha Nurhajarurahmah (Yayasan Literasi Sains Indonesia, 2025)
This community service activity aims to optimize Physical Education learning through a physical activity training and mentoring program at the IMMIM Islamic Boarding School Senior High School. The background to this activity is the limited variety of learning conducted by teachers and the low involvement of students in physical activities due to the busy academic and religious routines at the Islamic boarding school. The implementation method is carried out through four stages: preparation, training, mentoring, and evaluation. The preparation stage is carried out by developing training modules and evaluation instruments, while the training stage focuses on improving teacher competency and introducing a variety of physical activities to students. Mentoring is carried out directly during the lesson, followed by an evaluation to assess the effectiveness of the program. The results of the activity indicate that teachers gained increased knowledge and skills in managing more creative and enjoyable Physical Education learning. Meanwhile, students showed increased motivation and active participation in physical activities, and a culture of healthy and active living began to form in the Islamic boarding school environment. Overall, this community service program was able to make a real contribution to improving the quality of Physical Education learning while supporting the achievement of educational goals holistically. This activity is recommended to be continued on an ongoing basis and expanded to other schools with adjustments based on local wisdom.